Delayed versus early appendicectomy in adult patients with acute appendicitis: a retrospective study in Hospital Sultanah Nur Zahirah, Terengganu - Abdullah, Rusli (2014)
Introduction: One of the commonest intraabdominal diseases is acute appendicitis and requiring emergency surgery. Delaying appendectomy and treated medically did not show any increasing morbidity. Aim: This study compared the association and outcomes adult patients with acute appendicitis between delayed appendicectomy and early appendicectomy Method: This is a retrospective study of adult patients with acute appendicitis who underwent appendicectomy between 1st January 2012 and 31st December 2012 in Hospital Sultanah Nur Zahirah, Kuala Terengganu. The patients were divided into two groups according to the time of surgery after admission. The early group underwent appendicectomy done within 24 hours of admission and delayed group appendicectomy after 24 hours. These data included demographic, operative characteristic, clinical presentation, laboratory results, Alvarado score, histopathology result, days of meal, length hospital stay, duration of intravenous antibiotic, duration of the operation and postoperative complications were evaluated and compared. Results: A total of 536 patients in this study but only 436 patients were included in the study. There were 290 patients in the early group and 146 in the delayed group. There were no significant differences in clinical presentation except in rebound tenderness and guarding with highly significant in early group 31.7% (p=0.002) and 19% (p=0.02), respectively. The laboratory result, leukocytosis was highly significant in the early group 79% compared to 67.8% in the delayed group but there was no significant difference in graph shift to the left. The Alvarado score was significantly different between groups which were 48.6% and 37%, respectively in score more than 7. There were no significant differences in histopathology results between two groups. There were significant differences in days started meal, length of hospital stay, duration of intravenous antibiotic and duration of the operation with mean 1.18 days, 2.92 days, 1.97 days and 47.65 minutes, respectively in delayed group (p<0.05). Compared to early group mean 1.07, 2.26, 1.30 and 42.29, respectively. There were no significant differences in postoperative complications. Conclusion: Performing delayed appendicectomy after 24 hours from admission does not increase the complications rate and increase progression of the disease. However, delayed appendicectomy increases the days started meal, length of hospital stay, duration of intravenous antibiotic and duration of the operation.